Investigation of mechanical responses to the tactile perception of surfaces with different textures using the finite element method. (July 2016) - Tang, Wei; Zhang, Jiankai; Shi, Xiaolu; Zhang, Shaogang; Liu, Songyong; Zhu, Hua; Ge, Shirong
Tactile perception is essential for humans to perceive the world, and it usually results in mechanical responses from the finger. In this study, a nonlinear, viscoelastic, and multilayered finite element model of the finger was developed. The relationship between the mechanical responses within the finger and tactile perception while the finger scanned different surface textures was studied. The results showed that the sensitivity of tactile perception is affected by the peak value of von Mises stress, which is itself determined by the shape and density of a given texture. The von Mises stress varies periodically with time, and this variation depends on the periodicity of the texture. Displacement signals around Pacinian corpuscles have periodic variation. The period of displacement decreases as the density of the texture increases. The spectral centroid increases as the spacing of the texture decreases. The related mechanisms are discussed in this article.